Analisis Kebijakan Indonesia dalam Menerima dan Memberikan Penanganan Bagi Pengungsi dan Pencari Suaka Asal Afghanistan - Samuel Kevin Tjahjana; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations Diponegoro, 2022)
Indonesia is a country that does not hesitate to accept and provide treatment for refugees and asylum seekers who come from various countries, including the very large number of migrants from Afghanistan. This policy was implemented by the Indonesian government even though Indonesia has no legal obligation, still has domestic problems, and the assistance provided by IOM to deal with refugees is getting smaller. Through this research, the author will analyze the background of the Indonesian government's policy to receive and provide treatment for refugees and asylum seekers from Afghanistan. In analyzing this issue, the author will use the perspective of cosmopolitanism with data analysis techniques using the congruent method. The results show that Indonesia accepts and provides treatment for refugees and asylum seekers from Afghanistan because Indonesia wants to fight for the rights of all migrants from Afghanistan because all human beings are part of one humanitarian community regardless of their affiliation.